Inovasi Pendidikan dengan Menggunakan Model Deep Learning di Indonesia - Suwandi; Putri, Riska; Sulastri (CV. Kurnia Grup, 2024)
The deep learning model, as proposed by Abdul Mu`ti, emphasizes a mindful, meaningful, and enjoyable learning experience, allowing students not only to memorize but to deeply understand and internalize the material. This study aims to examine the implementation of the deep learning model in the context of primary and secondary education in Indonesia through a literature review method. Based on the analysis of various recent sources, it was found that this model contributes positively to enhancing critical thinking skills, active participation, and student engagement in the learning process. However, several challenges in its implementation were also identified, including limitations in infrastructure, teacher readiness, and the constraints of the traditional curriculum that hinder flexibility. This article offers recommendations to support more effective deep learning implementation, particularly by strengthening teacher training and providing adequate facilities. With the right support, this model holds great potential to optimize the quality of education in Indonesia, preparing a highly competitive generation.